Utilization of recycled carbide as adsorbent for adsorption of dyes and COD from textile waste - Karim, Muhammad Arief; Yuniar, Henny; Rabia, Kharien Hemalia Putri (Journal of Environmental Engineering and Landscape Management, 2025)
This study assessed the potential of carbide waste (CW), a by-product of the welding industry, as a cost-effective adsorbent for removing dyes and COD from textile wastewater. CW was prepared through drying, filtering, and shaping into 2 mm-thick tablets (3 mm diameter), followed by heating at 150 °C for 120 minutes. Characterization using FTIR and SEM-EDX confirmed functional groups like hydroxyl and carbonyl and significant surface morphological changes. Batch experiments achieved maximum color and COD removal efficiencies of 94.48% and 96.73%, respectively, at 75 g adsorbent dosage and 150 min contact time. Freundlich isotherm (R² = 0.9918 for color) indicated heterogeneous adsorption, and kinetic studies fit a pseudo-second-order model. The process was exothermic, spontaneous, and governed by physical adsorption. Regeneration trials showed COD removal efficiency remained 90% after four cycles. These findings establish CW as an efficient, sustainable adsorbent with promising environmental and industrial applications for textile wastewater treatment.